The Impact Of The Strategy Of Cognitive Discrepancy Schemes In The Achievement Of Students In The Second Grade Intermediate In The Arabic Grammar And The De- velopment Of Their Learning Patterns - Salman Al-Naimi, Mohsin Mawlood (Opción, 2019)
The present research aims to identify the effect of the strategy of cognitive discrepancy schemes in the achievement of intermediate students in the Arabic grammar and the development of their learning styles. In light of the research ob- jective, the researcher formulated three zero hypotheses. The researcher adopted the experimental design of the experimental test of the experimental group and the control group for the suitability of the nature of the research. The sample of the research was chosen from the second grade intermediate students in the middle of Omar bin Jandab in Tikrit for the academic year 2017-2018. The total number of students was 62 students, 31 students as experimental group (31) students as con- trol group. The researcher conducted the equivalence process on experimental and control groups in variables, previous achievement in grammar and age in months, intelligence and learning patterns. The researcher prepared the necessary inputs for his research and included the identification of the scientific material for the study, the formulation of the behavioral objectives of the specific scientific material, and the preparation of teaching plans for the scientific material by teaching the exper- imental and control groups. The research seeks two tools: the first is an achieve- ment test in the Arabic grammar, which is in the final form of (37) test paragraphs of a choice of multi-choice four alternatives, after verifying the veracity and level of difficulty and force of discrimination of its paragraphs. ). The second tool is the measure of learning which is in the final form of (15) questions and each question (3) alternatives and before each alternative (3) options are (apply to me to a large extent, apply to me to a small extent, do not apply to) Equation (Alpha - Kronbach).The experiment lasted two full weeks, and after the completion of the ex- periment, the tools were applied (the achievement test and the learning patterns scale). After processing the data statistically, the results showed that the experimental group, which was studied according to the strategy of cognitive conflicts, was superior to their peers in the control group in the achievement test. In the light of these findings, the researcher developed a number of conclusions, recommendations and proposals.